Experimental evidence that nestlings adjust their fledging time to each other in a multiparous bird. (October 2021) - Santema, Peter; Schlicht, Lotte; Sheldon, Ben C.; Kempenaers, Bart
Abstract : The transition from nestling to fledgling is a key moment in the development of altricial birds. Mortality immediately after fledging is typically high and selection should favour fledging strategies that maximize the chance of survival. While several studies have examined the influence of ecological conditions or nestling development on the timing of fledging, the question whether nestlings influence each other's behaviour has received little attention. We tested how fledging decisions of blue tit, Cyanistes caeruleus, nestlings depend on the behaviour of their nestmates. First, we show that in unmanipulated broods, fledging events within a nest were highly clustered and nestlings fledged closer in time to a sibling than expected if fledging events were independent of one another. We then experimentally tested whether nestlings adjust their timing of nest departure to the behaviour of their nestmates, by translocating nestlings to a brood that differed in age by 2 days. Nestlings that were 2 days younger than their adoptive brood advanced their fledging time such that they fledged close in time to a nestmate. Nestlings that were 2 days older than their adoptive brood significantly delayed their fledging time, but they were often the first to fledge and were not always followed close in time by a nestmate. We conclude that nestling blue tits have a strong propensity to leave the nest close in time to nestmates. The adaptive significance of this behaviour warrants further study. Highlights: The process of fledging in birds is associated with high risk of mortality. This should favour fledging strategies that improve survival chances. We show that blue tits fledged closer in time to a sibling than expected by chance. They also adjusted their fledging time when placed in a brood of a different age. The survival consequences of synchronous fledging warrant further study.